The Problem of changing Psychological Dynamics of Religious Conversion in the Boti Tribal Community, South Central Timor Regency - Tanaem, Kevin Putri Novera; Kiling, Indra Yohanes; Takalapeta, Theodora; Ruliati, Dr. Luh Putu (Journal of Health and Behavioral Science, 2025)
The problem of changing religions is an on going matter. This means that the conflicts or problems that occur do not end when the individual decides to change religions but continues after the individual changes religions. In fact, physical and psychological violence perpetrated as a result of changing religions continues to occur. Individuals who have decided to change religions are always labeled as infidels, sinners, apostates, and without opinion. When society or individuals are labeled like that, individuals will feel anxiety, fear, shame and depression within themselves, this is called a psychological impact. Things that happen will spur individuals to experience changes cognitively, emotionally and also interpersonal relationships. The purpose of this study was to determine the psychological dynamics of the Boti people who changed religions and to find out how to deal with anxiety and stress after changing religions. The method used is a qualitative method with observation and interview techniques. The results of this study indicate that the Boti people actually experience psychological dynamics after deciding to change religions, and participants also admit to experiencing a lot of positive emotions after changing religions.